Analisis Jalur Terdekat Menuju Bangunan Shelter Evakuasi Tsunami di Kota Padang Menggunakan Network Analyst - Shabrina, Nanda; Ahmad, Defri (Jurnal Pendidikan Matematika, 2024)
West Sumatra is one of the provinces in Indonesia that is prone to earthquakes due to the Great Sumatran Fault and the convergence of the Indo-Australian Plate and the Eurasian Plate beneath the sea to the west of the island of Sumatra. Padang is a city with earthquake potential due to the Semangko Fault, and one of the potential consequences is the occurrence of tsunamis. To minimize these impacts in Padang, tsunami evacuation buildings, known as shelters, have been established. Therefore, it is crucial for the community to be aware of the nearest routes to these evacuation shelters in Padang. One method employed is using Network Analyst. Network Analyst is a tool within the ArcGIS software, which is a Geographic Information System (GIS) developed by ESRI to manage, analyze, and visualize geographical data. By utilizing Network Analyst, the closest routes to the researched areas are generated. Network Analyst employs the Dijkstra's algorithm to solve routing problems and can be generated based on two criteria: distance and time. The result of the nearest route to the tsunami evacuation shelter in Batang Arau Subdistrict, South Padang District, is from SDN 29 Pebayan Penggalangan to Nurul Iman Mosque Padang, spanning a distance of 1585 meters. The analysis of the nearest route using Network Analyst is then compared with manually calculated results using the Dijkstra's algorithm. The difference between manual calculations and Network Analyst results ranges from 1 to 4 meters, approaching reality. This information can serve as a reference for determining the nearest routes to evacuation shelters in the event of a tsunami in Padang.